Telaah dimensi proses kognitif pada soal pengayaan buku teks bahasa Korea untuk penutur asing - Alfia Rizky Zulianty; Didin Samsudin; Risa Triarisanti; Arif Husein Lubis (Universitas Mulawarman, 2023)
This study aims to assess the application of cognitive processing dimensions to the enrichment questions in the Korean book entitled 아하 한국어 2/Aha Hanguko 2 which contains 141 questions in 12 chapters. The cognitive process dimension is divided into six levels with two categories, namely lower order thinking skills and higher order thinking skills. The method used in this research is qualitative by using textual analysis. The results of the research in the book are that the enrichment questions do not yet contain all levels of cognitive process dimensions because there are no questions at the C5 - Evaluation level. However, there are still questions with other higher order thinking skills categories, namely levels C4 - Analysis and C6 - Creating. The enrichment questions are still dominated by the level C2 - Understanding which is a category of lower order thinking skills. Based on the results of the research, it can be seen that the book does not contain enrichment questions with the level of dimensions of cognitive processes that are included in the category of higher order thinking skills optimally. This can have an impact on the lack of sharpening of students' critical thinking skills.